2018
DOI: 10.1111/jgs.15317
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Polypharmacy and Cognitive and Physical Capability: A British Birth Cohort Study

Abstract: ObjectivesTo investigate longitudinal associations between polypharmacy and cognitive and physical capability and to determine whether these associations differ with cumulative exposure to polypharmacy.DesignProspective birth cohort study.SettingEngland, Scotland, and Wales.ParticipantsAn eligible sample of men and women from the Medical Research Council National Survey of Health and Development with medication data at age 69 (N=2,122, 79%).MeasurementsCognitive capability was assessed using a word learning te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
89
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 33 publications
(76 reference statements)
8
89
1
7
Order By: Relevance
“…The main strength of this study is that it includes the entire population of older adults aged 65 years or older with polypharmacy in Sweden, followed up for 3 years. The monthly assessments of polypharmacy exposure provide better time resolution of the fluctuations in polypharmacy status than earlier survey‐based studies with longer time periods between survey waves . There are some notable limitations to the study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The main strength of this study is that it includes the entire population of older adults aged 65 years or older with polypharmacy in Sweden, followed up for 3 years. The monthly assessments of polypharmacy exposure provide better time resolution of the fluctuations in polypharmacy status than earlier survey‐based studies with longer time periods between survey waves . There are some notable limitations to the study.…”
Section: Discussionmentioning
confidence: 98%
“…Polypharmacy may not always be a chronic and persistent hazard, making it difficult to provide tailored interventions at the right time for older adults . Third, observational studies aiming at establishing a causal association between polypharmacy and subsequent health outcomes have seldom considered polypharmacy as a time‐varying or cumulative exposure based on the assumption that polypharmacy is by definition chronic . Yet, until now, this assumption has remained untested and there exists no consensual definition of what constitutes chronic polypharmacy .…”
mentioning
confidence: 99%
“…Older adults were more likely to report using a higher number of medications compared with adults ages 55 to 64. Previous studies showed polypharmacy was independently associated with a significant decline in cognitive and physical capability and increased risk of falls (14% increase in fall risk with the each medication added beyond four medications) . Therefore, targeting older adults for tapering unnecessary medication has potential health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is significantly greater in those with dementia and other chronic conditions. Future research should consider the additional impact of polypharmacy on the ageing process (107,108) . 2 The impact of generational resilience: Many of the cohort studies incorporate the postwar generation.…”
Section: Future Factors For Considerationmentioning
confidence: 99%